Tropical diabetic hand syndrome- a case report with a short review - Naqash, Mohd Mubarik; Ahmad, Feroze; Bhat, Arif Nabi; Jalalie, Umar; Najar, Rameez Raja (International Journal of Research in Medical Sciences, 2016)
Tropical diabetic hand syndrome (TDHS) encompasses an acute symptom complex found in patients of diabetes mellitus primarily in the tropical regions. The syndrome usually follows a minor trauma to the hand, may rapidly progress to gangrene, fulminant sepsis and may even be life threatening. The syndrome is less recognized and thus reported less often. The authors present here a case of Tropical diabetic hand syndrome (TDHS) in a middle aged female with a poor glycemic control. The patient was managed meticulously both by surgical debridement and proper, culture evidenced antibiotic therapy apart from routine diabetic management.